LITERASI TUBUH DAN ADAB ISLAMI BAGI ANAK TAMAN PENDIDIKAN AL-QUR’AN: MEMBANGUN KETAHANAN ANAK MELALUI EDUKASI SEKSUALITAS SEJAK DINI - Nurjanah, Titin; Fatoni , Nurul; Fauziah, Syifa (khidmatan, 2025)
This community service program aims to bolster the resilience of students at TPA At-Tauhiid, Metro Timur, through the reinforcement of body literacy and Islamic manners (adab). The initiative addresses the critical issue of children’s limited understanding of bodily boundaries and their vulnerability to potential sexual violence. Employing a Participatory Action Research (PAR) approach, the program actively engages teachers, parents, and students in a collaborative learning process. The intervention methods include interactive storytelling, thematic role-playing to practice refusing strangers, and focused group discussions. Additionally, educational posters illustrating safe and unsafe touches were displayed, and a new regulation was implemented requiring students to return home immediately after sessions to ensure their safety. The results demonstrate a significant improvement in the children's awareness of maintaining awrah (modesty), their ability to distinguish between safe and unsafe touches, and their assertiveness in suspicious situations. Moreover, the program successfully heightened the awareness of parents and teachers concerning the urgency of early sexuality education within an Islamic framework. In conclusion, integrating body literacy into the TPA curriculum serves as an effective preventive strategy for child protection and self-defense education.